2006
DOI: 10.1080/10408360500295626
|View full text |Cite
|
Sign up to set email alerts
|

BCL2Family of Apoptosis-Related Genes: Functions and Clinical Implications in Cancer

Abstract: One of the most effective ways to combat different types of cancer is through early diagnosis and administration of effective treatment, followed by efficient monitoring that will allow physicians to detect relapsing disease and treat it at the earliest possible time. Apoptosis, a normal physiological form of cell death, is critically involved in the regulation of cellular homeostasis. Dysregulation of programmed cell death mechanisms plays an important role in the pathogenesis and progression of cancer as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
152
1
35

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(197 citation statements)
references
References 402 publications
9
152
1
35
Order By: Relevance
“…No difference was observed in Bad protein levels between CD18/HPAF/Scr and CD18/HPAF/siMUC4 cells ( Figure 3A). MUC1 and rat Muc4 has been shown to decrease apoptosis in response to various insults also by enhancing the expression of Bcl-X L (Raina et al, 2006;Thomadaki and Scorilas, 2006;Workman et al, 2009). In contrast, we did not observe any difference in Bcl-X L protein levels after gemcitabine treatment of CD18/HPAF/Scr and CD18/HPAF/siMUC4 cells (data not shown).…”
Section: Muc4 Blocks Activation Of Intrinsic Apoptotic Pathwaycontrasting
confidence: 59%
See 2 more Smart Citations
“…No difference was observed in Bad protein levels between CD18/HPAF/Scr and CD18/HPAF/siMUC4 cells ( Figure 3A). MUC1 and rat Muc4 has been shown to decrease apoptosis in response to various insults also by enhancing the expression of Bcl-X L (Raina et al, 2006;Thomadaki and Scorilas, 2006;Workman et al, 2009). In contrast, we did not observe any difference in Bcl-X L protein levels after gemcitabine treatment of CD18/HPAF/Scr and CD18/HPAF/siMUC4 cells (data not shown).…”
Section: Muc4 Blocks Activation Of Intrinsic Apoptotic Pathwaycontrasting
confidence: 59%
“…Phosphorylation of Bad promotes its interaction with the scaffolding protein 14-3-3 and prevents its interaction with antiapoptotic Bcl-X L protein, leading to its sequestration in the cytosol and inhibition of its pro-apoptotic activity (Thomadaki and Scorilas, 2006). We found that MUC4 increases phosphorylation of Bad in CD18/HPAF/Scr cells in response to gemcitabine treatment.…”
Section: Muc4 Facilitates Sequestration Of Bad In the Cytosolmentioning
confidence: 65%
See 1 more Smart Citation
“…The intrinsic pathway is mediated by the mitochondria, and the BCL2 family of genes are central to regulating this mode of apoptosis (Thomadaki and Scorilas, 2006). Delta-tocotrienoltreatment of K562 cells induced the expression of several members of this family, namely the BAD, BCL2L1, BNIP3L, HRK and MCL1 genes.…”
Section: Log2 (Fc Of Group 2/control Group)mentioning
confidence: 99%
“…[62][63][64][65][66] Specifically, 95% of patients with CLL have overexpression of BCL-2, which may explain why these patients have lymphocytes with increased longevity. 67 Interestingly, 90% of melanoma patients also have elevated BCL-2 levels, which could be a contributing factor in why some melanoma patients seem to have treatment resistance, with melanoma cells capable of escaping immunosurveillance. 68,69 Another mutation commonly found in the CLL population is deletion of 17p, which is where the TP53 gene is found.…”
Section: Molecular Mechanisms and Genetics Of Lymphoma And Melanomamentioning
confidence: 99%